Igniting intersectoral collaboration in chronic disease management: a participatory action research study on epilepsy care in Ireland. Issue 4 (3rd July 2020) - Varley, Jarlath; Kiersey, Rachel; Power, Robert; Byrne, John-Paul; Doherty, Colin; Saris, Jamie; Lambert, Veronica; Fitzsimons, Mary
ABSTRACT: Models of care developed to improve the lives of people with chronic diseases highlight integrated care as essential to meeting their needs and achieving person (patient)-centered care (PCC). Nevertheless, barriers to collaborative practice and siloed work environments persist. To set in motion some groundwork for intersectoral collaboration this study brought two expert groups of epilepsy care practitioners together to engage in participatory action research (PAR). The expert practitioner groups were hospital-based epilepsy specialist nurses (ESNs) and community-based resource officers (CROs). The PAR highlighted, that while the participants share a mutual interest in caring for people with epilepsy, underdeveloped CRO-ESN relationships, arising from unconscious bias and ambiguity can result in missed opportunities for optimal care coordination with consequent potential for unnecessary replication and waste of finite resources. However, through dialogue and critical self-reflection, a growing emotional connection between the disciplines evolved over the course of the PAR. This allowed for buds of collaboration to develop with CROs and ESNs working together to tackle some of the key barriers to their collaboration.